Urban biomass and green hydrogen in Ecuador as a sustainable energy resource - Coello-Pisco, Silvia (2024)
Ecuador is some country rich in agricultural biomass that is not used at all. But this type of biomass has an ecological value that can impact the diet of the Ecuadorian population. What is viable is the use of urban biomass as a raw material to produce sustainable green hydrogen. The methodology is based on qualitative research (qualitative exegetical content) and quantitative research (elementary analysis of the substrate). The sample was 296 homes whose organic bio-waste was analyzed to determine the theoretical percentage of CH4. The results allowed us to obtain the stoichiometric equations of CH4, in which a value of 49,6% was found, and a PCI of 3878.77 kcal/kg. It is concluded that the intra-domestic urban biomass generated in Guayaquil homes can be replaced with an 80.74% possibility of being used to produce green hydrogen by applying biological technology (dark fermentation). Combining both technologies (hydrogen and biomass) contribute to reducing energy dependence on fossil fuels and water to generate electricity and reducing the carbon footprint by promoting circular, sustainable and sustainable energy production.